A feasibility study on Nature's Air an air cleaning device with ionizer - Biton, Dennis Paul L. (College of Engineering, 2000)
The Nature's Air air purifier is made up of many parts, many of which are pre-fabricated materials and others are small parts. The ionizer generator, turbo fan, GI casing, and filter are among the pre-fabricated materials. The product purifies air and at the same time, ionizes harmful radiation present in the surrounding air. A market study on the product identified the target market to be primarily households having an income which belongs to brackets A, B, and C. With the demand exceeding supply, the group established a market share of about 60% for the next five years. The product costs Php 12,000 and an aggressive marketing in the form of print media, brochures and product launch make it feasible for the product to penetrate the industry. The total marketing budget for the introduction of the product is about Php 3.7 million. The technical analysis of the production showed that the company will assemble the pre-fabricated parts coming from different suppliers. This kind of production will require two storage areas and 700 square meters of land for the first two years of operations. A total of 33 administrative and support staff and 79 production workers are needed on the first two years of operations. On the succeeding years, expansion of the production will entail additional workforce, in terms of 5 administrative and support staff and 100 production workers. One 8-hr. shift is needed for the production. The plant, having an area of 500 square meters located at Sucat, Parañaque, can accommodate all these requirements. The total project cost for the first four months of operations is about Php 83 million. In the organization and management study, the form of organization established to pursue the project is that of a corporation. It shall be composed of the Plant Manager, six department heads and support staff. A total of 33 administrative and support staff for the first two years of operations will be employed by the corporation. For the succeeding years, 38 administrative and support staff would make up the organization. The results of the financial analysis showed that the product is financially feasible and attractive. The project is profitable as shown by the financial ratios which also revealed the company is both liquid and solvent for the first five years of operations. The Net Present Value of the project amounts to around Php 263 million with an internal rate of return equal to 99%, compared to a Minimum Attractive Rate of Return of 25%, and a payback period of two months. A listing of the benefits and disbenefits in undertaking the project was provided in the Social Profitability Analysis. Far-reaching benefits to both the society and the chosen site and the local and national government were identified. These include the additional employment opportunities, payment of municipal, corporate and individual income taxes of the corporation. It can, therefore, be concluded that Nature's Air air purifier has a sufficient market, is technically feasible, is financially attractive, and is socially profitable to all entities affected.